Pengembangan Permainan Ludo Kimia Berbasis Android Sebagai Media Pembelajaran Pada Materi Reaksi Reduksi dan Oksidasi Kelas X SMA/MA - Ningsih, Puji Aptriyani Anggelia (Jurnal Pendidikan Kimia Undiksha, 2022)
This study aims to develop and determine the validity and practicality of the android based chemistry ludo game as a learning medium for the material of reduction and oxidation reactions. The type of research is Educational Design Research with the Plomp model which consists of three stages, namely preliminary research, prototyping stage, and assessment phase. This research is limited to the assessment phase, namely the small group test. The research subjects were 3 chemistry lecturers at FMIPA UNP, 3 engineering lecturers at FT UNP, 2 chemistry teachers, and 12 students in class XII MIPA SMAN 2 Batang Anai in the 2021/2022 academic year. The research instrument was a one to one evaluation questionnaire, a validity test questionnaire, and a practicality test questionnaire. The validity data were analyzed using the Aiken`s V formula and the practicality data were analyzed using the percentage formula. The results showed that the android-based chemical ludo game had content validity, construct validity and media validity with valid categories. Practicality to teachers as a whole is in the practical category, and practicality to students as a whole is in the very practical category. Based on the results of the study, it was concluded that the android-based chemistry ludo game as a learning medium for the material for the reduction and oxidation reactions of class X SMA/MA was valid and practical.